2012
DOI: 10.1007/s00208-012-0894-x
|View full text |Cite
|
Sign up to set email alerts
|

Liouville theorems for stable solutions of biharmonic problem

Abstract: Abstract. We prove some Liouville type results for stable solutions to the biharmonic problem ∆ 2 u = u q , u > 0 in R n where 1 < q < ∞. For example, for n ≥ 5, we show that there are no stable classical solution in R n when n+4 n−4 < q ≤ n−8 n −1 + .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 16 publications
(14 reference statements)
2
67
0
Order By: Relevance
“…It was shown there exists nontrivial finite Morse index solutions of (14) if and only if N ≥ 11 and θ ≥ θ JL . In [51] the nonexistence of stable solutions of (5) was examined. It was shown that there is no positive stable solutions of (5) provided either: N ≤ 8 or N ≥ 9 and 1 < θ < N N −8 + ε N where ε N is some positive, but unknown parameter.…”
Section: Theorem 2 (Fourth Order Scalar Equation)mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown there exists nontrivial finite Morse index solutions of (14) if and only if N ≥ 11 and θ ≥ θ JL . In [51] the nonexistence of stable solutions of (5) was examined. It was shown that there is no positive stable solutions of (5) provided either: N ≤ 8 or N ≥ 9 and 1 < θ < N N −8 + ε N where ε N is some positive, but unknown parameter.…”
Section: Theorem 2 (Fourth Order Scalar Equation)mentioning
confidence: 99%
“…Critical to our approach in the following result: Lemma 6. [51] Suppose that (u, v) is a stable smooth positive solution of (4) with p = 1. Then by Lemma 7, u is a positive stable solution of (5) and then the results of [51] imply there is some C < ∞ such that…”
mentioning
confidence: 99%
“…where we used (2.3) in the last step. For the second term on the right hand side of (2.20), applying the estimate (2.3) from [15], i.e., (∆u) 2 ≥ 2 p+1 u p+1 , and the fact that ∆u < 0 from [14] or [16], we have…”
mentioning
confidence: 99%
“…We use the idea of Moser and multiply (1.7) by uη 2 where η ∈ C ∞ 0 (R N ); see [16] and [17]. Note that as u ∈ L ∞ (R N ), by the regularity theory u ∈ C 4 (R N ).…”
Section: Preliminariesmentioning
confidence: 99%